Risk Factors of Elder Abuse: A Predictive Model for Elderly Abuse based on Demographic, Social, and Economic Risk Factors - Estebsari, Fatemeh; Latifi, Marzieh; Moradi Fath, Marjan; Sheikh Milani, Arezoo; Nasiri, Maliheh; Rahimi Khalifeh Kandi, Zahra (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Mistreatment of elderlies is a global concern in the field of public health and human rights. The primary objective of this study was to identify and analyze risk factors associated with elder abuse through the use of a regression model. The present cross-sectional study was conducted to determine the predictors of elder abuse in Tehran, the number of samples was calculated 425. Methods: Demographic Information Questionnaire and the Elderly Abuse Questionnaire with 49 items were used for this purpose. The Cronbach’s alpha was calculated 0.85 for the abuse in overall. Using univariate and multivariate linear regression models at a confidence interval of 0.95%. Results: The mean ± SD age of the participants was 67.44±8.01 years. Approximately 68.7% of the participants were male, while 31.3% were female. The results indicate that emotional abuse had the highest frequency of occurrence among the elderly, whereas physical abuse had the lowest. Among the factors studied, the living companion of the elderly (p< 0.001), education level (p< 0.001), financial independence (p< 0.001), and health status (p< 0.001) were found to be predictors of elder abuse. Conclusions: As demographic variables have been identified as risk factors for elder abuse, it is recommended that social welfare organizations, care systems, and policymakers implement measures to develop plans and programs aimed at reducing the risk of elder abuse, preventing it at the community level, and addressing barriers related to the improvement of demographic variables.